Evaluating Oral Health Status, Oral Lesions Prevalence, and Oral Health Impact Profile-14 among Tobacco Industry Workers - Grandhi Srujananjali; K. Ramya; Roja Lakshmi Karri; Krishna Sahi Bonthagarla; Akkineni Bhavya Sree; Yannam Mounika (Indian Journal of Dental Sciences)
Background: Maintaining optimal oral health is critical for general well-being, particularly in occupational settings where unique hazards may impact oral health. The purpose of the present study is to comprehensively examine the oral health implications among tobacco industry workers, considering demographic factors, deleterious habits, oral health measures, and quality of life indicators. Materials and Methods: The study comprised 180 participants employed in the tobacco industry were included in the study. Demographic data, tobacco-related habits, and oral health parameters including decayed, missing, filled teeth (DMFT), community periodontal index (CPI), loss of attachment (LOA), oral hygiene index-simplified (OHI-S), and oral health impact profile (OHIP-14) scores were assessed. Results: The study revealed a predominantly younger, lower-income demographic with significant tobacco use. Oral health assessment indicated moderate dental caries (DMFT: 8.65), low-to-moderate periodontal issues (CPI: 2.28, LOA: 1.49), and fair oral hygiene (OHI-S: 1). Notably, a moderate level of oral health impact was observed (OHIP-14: 10.51), with physical pain and disability having the highest impact. The prevalence of oral lesions, although relatively low (84.4% with no lesions), suggests the importance of tailored oral health management. Conclusion: These findings emphasize the importance of focused interventions and ongoing research to enhance overall oral health and quality of life among tobacco industry workers. Public health initiatives, educational programs, and tailored interventions are warranted to address the identified oral health challenges in this population.